Preventive effect of Lactobacillus reuteri CRL1324 on group B Streptococcus vaginal colonization in an experimental mouse model - de Gregorio, Priscilla Romina (2015)
AIMS: To assess the preventive effect of different intravaginal (i.va.) doses of Lactobacillus reuteri CRL1324 against vaginal colonization by Group B Streptococcus (GBS) in a murine experimental model. METHODS AND RESULTS: The major virulence factors of four vaginal GBS clinical isolates were determined to select the most virulent strain and set up a murine model of streptococcal vaginal colonization. Later, the effect of four and seven doses of 10(8) viable cells of Lact. reuteri CRL1324 i.va. administered, prior to the GBS challenge was studied. Seven doses of lactobacilli were able to significantly reduce the number of viable GBS cells, while four doses showed no preventive effect. Both doses reduced the leucocyte influx induced by GBS. Seven doses caused a slight increase in the Lact. reuteri CRL1324 vaginal colonization compared with four doses and reduced murine vaginal pH compared to control mice. CONCLUSIONS: Lactobacillus reuteri CRL1324 evidenced a preventive effect on GBS vaginal colonization in an experimental mouse model. SIGNIFICANCE AND IMPACTS OF THE STUDY: Maternal GBS colonization is one of the most important risk factors for developing disease in newborns. Lactobacillus reuteri CRL1324 could be considered as a new biological agent to reduce infections caused by this micro-organism.